Objektifikasi Dan Perlawanan Perempuan Dalam Novel Rara Mendut Karya Y.B. Mangunwujaya: Analisis Wacana Kritis Sara Mills - OCTAMA DWITANINGSIH; Dwi Susanto; Supana (Badan Riset dan Inovasi Nasional (BRIN), 2024)
This research examines the power built through the language of objectification and women's resistance in the novel Rara Mendut by Y.B. Mangunwijaya. The author wass not only known as a writer, but also a social fighter who devotes much of his attention to the little people. The story of Rara Mendut is based on historical background that talks about a looted slave who refused to be the concubine of Tumenggung Wiraguna, a Mataram commander. He was described as a brave figure and is not afraid to voice his thoughts and opinions. By using the Sara Mills model of critical discourse analysis approach, the researcher reveals the position and role of women in the text as well as the author's efforts to convey a message through female characters. Even though in the text, women are used as objects to be controlled and exploited, women are shown as subjects who show control within themselves to fight injustice.